2008
DOI: 10.1007/s10722-008-9374-2
|View full text |Cite
|
Sign up to set email alerts
|

Oleaster (var. sylvestris) and subsp. cuspidata are suitable genetic resources for improvement of the olive (Olea europaea subsp. europaea var. europaea)

Abstract: Oleaster (var. sylvestris) and subsp. cuspidata are suitable genetic resources for improvement of the olive Abstract The olive belongs to Olea, a complex genus and to a species with six subspecies. Subsp. europaea includes both the cultivated olive and the oleaster, the wild ancestor of the olive. Little is known on the phenotype of fruits from subsp. cuspidata. We the possible uses of these taxa for breeding both the olive and brown olive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 27 publications
5
32
1
Order By: Relevance
“…The monounsaturated fatty acids (MUFAs) are of great importance because of their high nutritional value and positive effect on the oxidative stability of oils [32]. Oleic acid was found to be the main MUFA in the VOO composition of the cultivars as well as of Oleasters K and M, constituting 60.6 to 66.9% of the total fatty acid content ( Table 2), values comparable to those found by Hannachi et al in olive oils from cultivars and oleasters [33]. However, the oleic acid contents found in the present study for the cultivated olive oils seem to be higher than those reported by Krichène et al [34] and lower than those obtained by MahjoubHaddada et al [35].…”
supporting
confidence: 75%
“…The monounsaturated fatty acids (MUFAs) are of great importance because of their high nutritional value and positive effect on the oxidative stability of oils [32]. Oleic acid was found to be the main MUFA in the VOO composition of the cultivars as well as of Oleasters K and M, constituting 60.6 to 66.9% of the total fatty acid content ( Table 2), values comparable to those found by Hannachi et al in olive oils from cultivars and oleasters [33]. However, the oleic acid contents found in the present study for the cultivated olive oils seem to be higher than those reported by Krichène et al [34] and lower than those obtained by MahjoubHaddada et al [35].…”
supporting
confidence: 75%
“…In particular, a few ecotypes from Fars and Chahar-Mahal showed alleles characterizing all cuspidata plants, suggesting that hybridization between the two forms europaea × cuspidata may have been possible and may have naturally occurred in places where these forms may have cohabited for a long time. Further evidences of spontaneous hybridization occurring between cultivated plants and local cuspidata plants have been previously reported in South Africa [41]. It may be speculated that the barrier between the two subspecies is not complete and that some Iranian ecotypes may have been derived from a gene flow from cuspidata to local forms of europaea .…”
Section: Discussionmentioning
confidence: 78%
“…cuspidata (Wall. ex G. Don) Cif is also available (Hannachi et al 2009). Olive cultivars had a higher oil content than fruits of oleaster and subsp.…”
Section: A Genotypementioning
confidence: 99%